The Implementation of Autonomy Learning in English Teaching Module of the Merdeka Curriculum - Zulfa, Rubbyanti; Afriyanti, Rika; Suharni, Suharni (International Journal of Language Pedagogy, 2024)
This research aims to find out how the application of Autonomy learning in English teaching modules. Participants of this study were seventh grade students at SMP Negeri 20 Padang which amounted to 276 students divided into 9 classes. In determining participants, researchers used purposive sampling technique because researchers only examined classes that applied learning independence so that participants were obtained in 1 class, namely class VII.4 which amounted to 29 people. Data collection techniques using video recording and observation checklist, then observed and analyzed based on the application of student learning independence in each class in the process of English learning activities, and the results showed that every student of the 29 students who had been studied had learning independence. Thus, it can be concluded that students can implement learning independence in the process of learning English.